ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN PERMASALAHAN IDENTITAS TRIGONOMETRI BERDASARKAN KRITERIA WATSON DITINJAU DARI GAYA BELAJAR - Susanto, S; Guswanto, Ervin; Trapsilasiwi, Dinawati (Kadikma, 2018)
This reseacrh aim to analyze the students mistakes doing math problems on subject of the Identity of trigonometry using Watson Criteria Analysis viewed from learning styles. This research use a qualitative approach and the type of research is descriptive. Subject in this research are six students in XI MIPA 1 of Senior High School 1 Rambipuji. Data collection was performed by the method of test and interview. In the class, there are 7 students with Visual learning style type, 20 students with Auditorial style type, and 7 students with kinesthetic style learning style, and 1 student not attending school. The result of research showed that based on Watson Criteria in the subject of high mathematic logic intelligence was 7,48% inappropriate data, 8,41% inappropriate procedure, 9,45% ommited data, 17,64% ommited conclusion, 21,50% response level conflict, 7,48% undirected manipulation, 28,04% skills hierarchy problem, 0% above other. Keywords: Identity of Trigonometry Problem, Watson’s Error Analysis, Learning Styles